Drug use in French children: a population-based study. Issue 10 (14th May 2015) - Bénard-Laribière, Anne; Jové, Jérémy; Lassalle, Régis; Robinson, Philip; Droz-Perroteau, Cécile; Noize, Pernelle
Abstract : Background and objective: To provide an overview of drug use in outpatient children in France, a population-based study using a national reimbursement claims database representative of 90% of the French population was conducted. Design: Cross-sectional study performed between January and December 2011 using the EGB database ( Echantillon Généraliste de Bénéficiaires ), a 1/97th sample of the national healthcare insurance system beneficiaries. Drug use in children <18 years old was estimated through reimbursements for prescribed drugs excluding vaccines. Prevalences of use were calculated for different levels of the Anatomical Therapeutic Chemical classification by considering as users children who had at least one reimbursement during the study period. Results: In 2011, 133 800 children were included in the study. The overall prevalence of drug use was 84% and the median number of different drugs per child was 5. Drug use was greatest in children aged <2 years. The most widely used drugs were paracetamol, systemic anti-infectives, nasal corticosteroids and decongestants, and anti-histamines. 21% children <2 years received domperidone. Conclusions: There is widespread use of medicines that are unlikely to be effective and may have significant toxicity in French children. Irrational use of medicines appears to be greatest in children aged 5 years and under.